Eksplorasi Geokimia untuk Menentukan Daerah Prospek Mineralisasi Emas Tipe Urat Epitermal: Studi Kasus di Daerah Tompaso, Kabupaten Minahasa Selatan, Sulawesi Utara - Idrus, Arifudin; Fadlin; Hartono, Hill Gendoet (BRIN Publishing, 2021)
North Sulawesi, including the Tompaso region, South Minahasa district, is a part of the magmatic belts hosting potential hydrothermal ore deposits. This study is aimed to determine the prospect area for epithermal vein-type gold mineralization, based on geochemical exploration including rock and BLEG (Bulk Leach Extractable Gold) stream sediment geochemistry. Mapping of geology, alteration and vein direction, sampling (ore/rock and stream sediment), and geochemical analysis were performed. Gold in rock samples was analyzed by FA/AAS, and other elements were detected by AAS, while BLEG samples were analyzed using the cyanide leach and AAS methods. The study area is occupied by andesitic lava and diorite, which are suffered by silica-clay, argillic and propylitic alteration. An integration of geological mapping, alteration zones and vein direction with lithogeochemical survey enables to determine the prospect areas, which consist of Asam and Polangkok prospects. At the Asam prospect, the ore sample contains gold up to 0.03 ppm, where the gold anomaly in BLEG samples show a threshold of 13.52 ppb Au. At the Polangkok prospect, two NW-SE trending veins (P1 and P2 Veins) were discovered with a width of up to 5 m. Vein P1 and P2 contains of up to 0.31 and 0.16 ppm Au, respectively. Mineralization at the Polangkok prospect coincides with Ag anomaly of BLEG samples with a threshold of 67.18 ppb. The two prospect areas are recommended for follow-up exploration.